Адміністративно-правове забезпечення контролю за діяльністю суб’єктів господарювання, що здійснюють перевезення пасажирів автомобільним транспортом в Україні : автореферат дисертації - Хоробрих, П. М.; Khorobrykh, P. M.; Бурило, Ю. П. - науковий керівник (Харківський національний університет внутрішніх справ, 2024)
Визначено сутність та зміст діяльності суб’єктів господарювання, що здійснюють перевезення пасажирів автомобільним транспортом як об’єкту контролю. Охарактеризовано поняття та особливості контролю за діяльністю суб’єктів господарювання, що здійснюють перевезення пасажирів автомобільним транспортом. Досліджено види контролю за діяльністю суб’єктів господарювання, що здійснюють перевезення пасажирів автомобільним транспортом. Проаналізовано правові засади контролю за діяльністю суб’єктів господарювання, що здійснюють перевезення пасажирів автомобільним транспортом, та визначено місце серед них адміністративноправових норм. З’ясовано значення, завдання та функції контролю за діяльністю суб’єктів господарювання, що здійснюють перевезення пасажирів автомобільним транспортом. Наведено перспективні напрями вдосконалення адміністративного законодавства, яке регламентує контроль за діяльністю суб’єктів господарювання, що здійснюють перевезення пасажирів автомобільним транспортом.

The thesis provides a theoretical generalization and a new solution to the scientific problem, which consists of determining the essence and disclosure of administrative and legal support features for control over business entities' activities in transporting passengers by road in Ukraine. It has been argued that the activities of business entities carrying out the transportation of passengers by road in Ukraine are multifaceted and cover various aspects: organization of the transport process, management of the fleet of vehicles, maintenance of their technical condition, compliance with safety requirements, and provision of services of proper quality to passengers. Accordingly, control over the activities of business entities carrying out the transportation of passengers by road is a necessary component to ensure an appropriate level of safety, compliance with technical standards, and protection of consumer rights. It has been proven that control over the activities of business entities carrying out passenger transportation by road is a multifaceted and complex system, which includes numerous aspects of inspection and monitoring - from technical requirements for vehicles to social and environmental standards. The development of this system, the introduction of new technologies, and the strengthening of international cooperation will improve the quality of transport services, ensure the safety of passengers, and create a sustainable and competitive transport system in Ukraine. It has been emphasized that control over business entities' activities carrying out passenger transportation by road is multifaceted and covers various aspects: from compliance with safety rules and the technical condition of transport to the protection of consumer rights. This allows you to ensure the proper level of road safety, high quality of services, and minimization of the negative impact on the environment. It has been determined that depending on specific, relatively independent spheres of social relations that are subject to the regulatory influence, it is possible to distinguish such types of control over the activities of business entities that carry out the transportation of passengers by road as control over compliance with the requirements of the legislation in the field of transport, licensing and safety of transportation, financial control, environmental control, as well as control over the observance of consumer rights. Depending on the subject composition and scale of the implementation of the relevant control activities, state control, control carried out by local self-government bodies, and departmental and public control are distinguished. It has been noted that an important direction for improving legislation is developing long-term strategies for the development of the road passenger transportation industry. Such strategies should include anticipating changes in traffic flows, adopting the latest technologies, and adapting to changes in societal needs. In particular, it is necessary to take into account trends towards urbanization, the development of cities, and agglomerations.
Administrative and legal provision of control over the activities of business entities engaged in the transportation of passengers by road transport in Ukraine
Keywords: Україна; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.07; пасажирські перевезення; автомобільний транспорт; суб’єкти господарювання; державна політика; правове регулювання; законодавче забезпечення; адміністративний статус; контроль; координація; взаємодія; Ukraine; passenger transportation; road transport; business entities; state policy; legal regulation; legislative support; administrative status; control; coordination; interaction